A methodology for the children of 6 years of life to get familiar with Chess by means of Physical Education lessons - Mercedes Miló Dubé; Yarima Laffita Paulin; Danay Quintana Rodríguez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
In this research it is designed a methodology to favor the process of identification of the Children of 6 years of life with Chess by means of Physical education lessons. This product will facilitate the preparation for the children before receiving this subject in primary schools. For the development if this research it was necessary to select a sample of some children of 6 year of life with the corresponding teachers as well as some experts and specialists on the topic. In the processing of information, it was used some methods, such as the historical logical, analytical syntetical, hypothetical deductive and the systemical structural functional. As empirical methods it was used documents, interviews, surveys and the observation. It was also employed the criteria of experts, the experiments and validated through the McNemar test. This methodology has been validated and put into practice with very positive results so far.